The Distally Based Dorsal Metatarsal Artery Perforator Flap: Vascular Study and Clinical Implications - van Alphen, Nick A.; Laungani, Alexis T.; Christner, Jodie A.; Lachman, Nirusha; Carlsen, Brian T.; Saint-Cyr, Michel (Journal of Reconstructive Microsurgery, 2016)
Background Intrinsic flaps based on the dorsal metacarpal arteries are useful for coverage of dorsal hand, finger, and thumb defects. The purpose of this study was to explore the anatomy of the dorsal metatarsal arteries (DMtAs) in the foot to help define their clinical utility. We observed the size and numbers of distal perforators from the DMtAs and quantified the vascular perfusion pattern of the DMtA perforator across the skin.Methods Ten fresh cadaver feet were injected with latex and dissected to assess the size and number of distal perforators from the DMtAs. Five DMtA perforator flaps were injected with methylene blue to visualize and quantify the vascular territory of the skin flap to understand the clinical possibilities. In addition, a clinical case is described and shown.Results Ten fresh cadaver feet were dissected. The first DMtA was absent in two specimens and the second, third, or fourth DMtA was absent in one specimen each. The available DMtAs had between two and five cutaneous perforators supplying the skin (average, 3.7 perforators per DMtA). The largest perforators to the skin were always seen in the distal half of the DMtA and ranged from 0.4 to 0.8 mm (average, 0.5 mm). Methylene blue injections showed an average flap surface of 21.6 × 47.6 mm.Conclusion This cadaveric study demonstrates the usefulness of the DMtA perforator flap. The flap is a valuable addition to the arsenal of flaps to cover the dorsum of the toe, webspace, or defects exposing tendons on the distal dorsum of the foot.
Keywords: perforator flap; dorsal foot flap; anatomy; cadaver study; dorsal metatarsal artery